Adaptation - Jacobs, Robert Nelson; Roth, Eric; Robinson, Phil Alden; The Writers Guild Foundation; First Light Video Publishing; TMW Media Group, Inc. ([California] : The Writer Guild Foundation : TMW Media Group, Inc. (distributor), 2004)
This program teaches hoe to highlight the good parts and trouble spots in a script, research, visualizing and dramatization, non-fiction vs. fiction, the encho effect, online research vs. physical, changing directions, genre material, staying fresh and externalizing characters thoughts
Title from title screen
Tape 4: Adaptation
Photography: Andrea Cimini
Keywords: Film adaptations; Motion pictures and literature; Motion pictures -- Plots, themes, etc